Studies of structural and electrical properties of La-Mg-Mn-Ti-O ceramic - Mohamad Hanif, Siti Hashimah; Sinin, Aaliyawani Ezzerin; Chyi, Josephine Liew Ying; Primus, Walter Charles; Matori, Khamirul Amin (Hanyang University Ceramic * Processing Research Center, 2023)
The samples with chemical formula La1-xMgxMn0.4Ti0.6O3 (x = 0.30, 0.40 and 0.50) were synthesized using solid-state reaction method. XRD of the samples shown the samples pattern attributed to the cubic structure with ‘a’ = 3.8943 and its space group Pm3m. The SEM images display microstructure of the sample were porous and the grains are merged with unequal sizes distributed inhomogeously throughout the samples with irregular boundaries. The sample of x = 0.4 was the most porous than the others. The electrical properties were measured using LCR meter with the frequency range from 0.01 Hz until 100 KHz and in a temperature range of 313 K until 373 K. The electrical properties of the samples were study by analyzed the dielectric constant, ε’, dielectric loss, ε”, and tan δ. The results for dielectric constant and dielectric loss showed the higher values were located at lower frequency region which suggest that the samples were having interfacial polarization. Tan δ shows the lower value at higher frequency and lower temperature. By doping Mg, it decreases the dielectric loss and increasing the Mg doping it increases the dielectric constant.